Guihaia heterosquama, a new species of coryphoid palm (Arecaceae) from Chongqing, China - Li, Xianyuan; Peng, Hui; He, Xi; Li, Zhineng; Wu, Di (Phytotaxa, 2019)
Guihaia heterosquama X. Y. Li, a new species from Chongqing, China, is described and illustrated. Guihaia heterosquama is similar to G. grossifibrosa and G. argyrata both in the shape of the leaf blade and flower structure, but it can be easily distinguished by its leaf scales, leaf sheath fibers and hastula. Notably, Guihaia heterosquama differs from all the reported species of Guihaia by the presence of a distinct pistillode in the male flower.